ChemInform Abstract: Palladium‐Catalyzed Mizoroki—Heck Type Reaction with Aryliodine Diacetates Using Hydrazone Ligand. Issue 7 (18th February 2014) - Mino, Takashi; Watanabe, Kohei; Abe, Taichi; Kogure, Taketo; Sakamoto, Masami
Abstract The palladium‐catalyzed Mizoroki—Heck type reaction of substituted aryliodine diacetates (I) with olefins of type (II) affords (E)‐olefins (III).